Using "Home" to Explain the Factors Affecting Residential Satisfaction The Case of Panama's Heterogeneous Environments During The Covid-19 Crisis. Issue 5 (20th October 2022) - García de Paredes, Pablo
ABSTRACT: This study's goal is to explore the representations of home that underlie residential satisfaction during the Covid-19 crisis, by developing new tools for housing research. We hypothesize that the concept of home helps explain the different experiences of social groups during the confinement period, and its effect on residential satisfaction. To test our hypothesis, we developed a mixed-methods approach departing from 135 original surveys. . First a quantitative index was created, measuring four groups of home dimensions; the inside of home (1), the outside connection (2), home as protection against stressors (3) and home as a place for positive adaptation (4). Secondly, we used content analysis to enlarge the explanatory power of the index. Our results show the index is a viable tool for exploring the different experiences of confinement. Our method potentially improves research on residential satisfaction leading to more resilience, and better design guidelines for professionals.